Penyuluhan Anemia Dan Pemeriksaan Hemoglobin Pada Ibu Hamil Di Puskesmas Sungai Sembilan - Fatmawati; Ariza Julia Paulina; Fridayenti (LPPM UMRI, 2023)
Maternal Mortality Rate (MMR) is an indicator to assess the degree of a nation, especially women. MMR according to the results of the 2012 Indonesian Demographic and Health Survey in Indonesia was 359 per 100,000 live births. The most common causes of maternal death in the city of Dumai are ante partum hemorrhage and preeclampsia in 3 cases each. The purpose of this service activity is to increase knowledge and understanding of anemia in pregnant women and to find out the status of anemia in pregnant women at the Sungai Sembilan Health Center, Sungai Sembilan District, Dumai Regency. In addition to counseling activities, a pre-test and post-test were carried out using 10 multiple-choice questions to assess the knowledge of the community, totaling 30 people. Overall, more than 50% of participants already have a good level of knowledge about anemia in pregnancy. There were 33% of participants who had a hemoglobin level <11 which means they had mild anemia. By conducting counseling about anemia and hemoglobin examination, it is hoped that it can increase the knowledge of the community at the Sungai Sembilan Health Center, Sungai Sembilan District, Dumai Regency.